Analysis of XR Research in Brazil from 21 Years of SVR Publications - Teixeira, João Marcelo; Peres, Fabiana Frata Furlan (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2020: Anais do XXII Simpósio de Realidade Virtual e Aumentada, 2020)
Although Virtual Reality technology was first developed almost sixty years ago, there has been little survey work giving an overview on how research in VR, AR and MR evolved in Brazil along with their future trends. We provide such analysis by reviewing the development made since the first WRV event, back in 1997, until the last SVR, in 2019. The 21 event editions may help understand how the area was explored and provide a roadmap for future research. The 557 full papers analyzed were compiled into an open catalog, available on the internet. It features important filter capabilities, enabling the quick selection of papers based on citation number, conference topic, area of application, user experiments, statistical analysis and so on. We hope this tool to be of great value to the field, and also for helping researchers decide which topics should be explored when they are beginning their own studies in the area.